2019
DOI: 10.18203/2349-2902.isj20191280
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy in sickle cell haemoglobinopathies

Abstract: Background: Sickle cell disease is one of the common haemoglobinopathies in the world. Among its various clinical presentations, splenic complications are associated with high morbidity and substantial mortality, the only effective preventive strategy for which is prophylactic splenectomy. The aim of the present study was to observe the safety and effectiveness of splenectomy to prevent frequent requirement of hospitalizations, blood transfusions and splenic complications in patients of sickle cell disease.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Although the exact mechanism of high HbF in the Indian population is still not understood, it has been well documented that HbF is a very powerful modulator of the clinical and the haematologic features of sickle cell anemia. It has been found that the Saudi-Indian and Senegal haplotypes of HBB-like gene cluster have exceptionally higher HbF levels, hence associated with milder disease and lesser episodes of crisis 32 . In our study, we found that there was a higher level of an average of HbF in patients with splenomegaly (14.90±5.08) compared to those with a normal spleen (12.12±4.12).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism of high HbF in the Indian population is still not understood, it has been well documented that HbF is a very powerful modulator of the clinical and the haematologic features of sickle cell anemia. It has been found that the Saudi-Indian and Senegal haplotypes of HBB-like gene cluster have exceptionally higher HbF levels, hence associated with milder disease and lesser episodes of crisis 32 . In our study, we found that there was a higher level of an average of HbF in patients with splenomegaly (14.90±5.08) compared to those with a normal spleen (12.12±4.12).…”
Section: Discussionmentioning
confidence: 99%
“…These indications can cause pain, which may lower QoL. If these patients undergo a splenectomy, this could lower the frequency of their hospitalization for blood transfusions, provide relief from an enlarged spleen and its symptoms, and prevent recurrent acute splenic sequestration crises and their complications [ 25 ]. However, we could not find an association between QoL and splenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative hospital stay after a splenectomy procedure can vary, with an average length between 3 and 9 days. 18 , 19 , 20 However, a study has reported that laparoscopic splenectomy for benign hematological disorders is significantly associated with prolonged postoperative hospital stays and greater blood loss. 17 In our study, most patients had a hospital stay period between 2 and 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…This time period is similar to that in the general population and less than that previously reported in patients with hematological diseases who underwent splenectomy. 18 , 19 , 20…”
Section: Discussionmentioning
confidence: 99%